2012
DOI: 10.1093/icvts/ivs275
|View full text |Cite
|
Sign up to set email alerts
|

Storage of saphenous vein grafts prior to coronary artery bypass grafting: is autologous whole blood more effective than saline in preserving graft function?

Abstract: A best evidence topic in thoracic surgery was written according to a structured protocol. The question addressed was: 'Is storage of saphenous vein grafts in autologous whole blood prior to coronary artery bypass grafting (CABG) more effective than storage in saline in preserving graft function?' Altogether more than 580 papers were found using the reported search, of which, 10 represented the best evidence to answer the clinical question. The authors, journal, date, country of publication, patient group studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…It was concluded that room-temperature saline was detrimental to vascular endothelium, and both normal saline and autologous whole blood impair smooth muscle function, relative to a buffered saline solution such as University of Wisconsin solution. 18 …”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that room-temperature saline was detrimental to vascular endothelium, and both normal saline and autologous whole blood impair smooth muscle function, relative to a buffered saline solution such as University of Wisconsin solution. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro and animal models have suggested that these vein graft preservation solutions may have important differences, they have not been compared in clinical studies. 3 We performed an observational comparative-effectiveness evaluation of various vein graft preservation solutions using data from a large randomized clinical trial of patients undergoing CABG surgery. We described the patterns of use of vein graft preservation solutions in clinical practice.…”
mentioning
confidence: 99%
“…To enhance the anticoagulant effect of these solutions, heparin is often added to the solution [5]. The action of antithrombin is accelerated by 1,000 times under the existence of heparin; thus, the effectiveness of the anticoagulation mechanism of heparin increases rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the anticoagulant effect of these solutions, heparin is often added to these solutions [5]. …”
Section: Introductionmentioning
confidence: 99%